Bank Liquidity in Disstressed Macro - Economic Conditions: The Case of Zimbabwe (Global Journal of Management and Business Research, 2020)
The bank liquidity phenomenon remains an unending theme of much debate among banking sector officials and the general banking public since it has the tenacity to derail economic activities in the event of chronic macro-economic fluctuations. Unstable macro economic environments are a formidable threat to bank liquidity positions as they play a significant role in deteriorating banks#x2019; assets value which often diminishes banks#x2019; liquidity.
Keywords: bank liquidity; liquidity ratios; macro-economic factors; distressed economic environment; regressors